Aktivitas Antioksidan Minuman Daun Beluntas Teh Hitam (Pluchea indica Less-Camelia sinensis) - Paini Sri Widyawati; Tarsisius Dwi Wibawa Budianta; Yesiana Dwi Wahyu Werdani; Maria Olivia Halim (agriTECH, 2018)
The research was conducted to explore the potency of pluchea leaves-black tea drink as antioxidant at various proportions. The research used a single factor randomized block design of pluchea leaves and black tea proportions, including 100:0; 75:25; 50:50; 25:75; and 0:100% (w/w). Each of it was repeated five times. The parameters observed in this study were secondary metabolites, total phenolic, total flavonoids, free radical DPPH scavenging activity, and iron reducing power. The data were statistically analyzed using Analysis of Variance (ANOVA) at α = 5%, if the analysis showed a significant effect then it was continued with Duncan's Multiple Range Test (DMRT). Data was stated as mean ± standard deviation. The results showed that the secondary metabolites containing in drink from pluchea leaves and black tea at various proportions were alkaloids, flavonoids, phenolics, saponins, tannins, and cardiac glycosides. The increasing of black tea proportion in samples added the intensity of alkaloids, phenolics, flavonoids, saponins, and cardiac glycosides compounds detected, but the tannins were decreased. These secondary metabolites were correlated with total phenolic content (TPC) and total flavonoid content (TFC). The increasing of black tea proportion in drink significantly decreased DPPH free radical scavenging activity and iron ion reducing power, except for 100% black tea proportion. Tannin compounds seems determining antioxidant activity.  Based on coefficient correlation between TPC or TFC and DPPH free radical scavenging activity or iron ion reducing power, the result showed that DPPH free radical scavenging activity was dominantly contributed by TPC and iron ion reducing power was determined by TPC and TFC. ABSTRAKPenelitian ini dilakukan untuk mengetahui potensi minuman daun beluntas teh hitam sebagai antioksidan pada berbagai proporsi. Penelitian ini menggunakan rancangan acak kelompok satu faktor, yaitu proporsi daun beluntas teh hitam meliputi 100:0; 75:25; 50:50; 25:75; dan 0:100% (b/b). Tiap faktor diulang sebanyak 5 kali. Parameter yang diamati pada penelitian ini meliputi kandungan metabolit sekunder, total fenolik (TPC), total flavonoid (TFC), kemampuan menangkal radikal bebas DPPH, dan kemampuan mereduksi ion besi. Data dianalisis secara statistik dengan Analysis of Variance (ANOVA) pada α = 5%, jika terdapat beda signifikan dilanjutkan dengan uji Duncan's Multiple Range Test (DMRT). Data dinyatakan dengan rata-rata ± standar deviasi.  Hasil menunjukkan bahwa metabolit sekunder yang terkandung dalam minuman daun beluntas teh hitam pada berbagai proporsi adalah alkaloid, flavonoid, fenolik, saponin, tannin, dan kardiak glikosida. Peningkatan proporsi teh hitam menambah intensitas senyawa alkaloid, fenolik, flavonoid, saponin, dan kardiak glikosida yang terdeteksi, tetapi kandungan senyawa tannin berkurang. Kandungan metabolit sekunder ini berkorelasi dengan total fenolik (TPC) dan total flavonoid (TFC). Peningkatan proporsi teh hitam dalam minuman menurunkan kemampuan menangkal radikal bebas DPPH dan kemampuan mereduksi ion besi, kecuali pada proporsi teh hitam 100%. Kandungan senyawa tannin dalam minuman menentukan aktivitas antioksidan. Berdasarkan koefisien korelasi antara TPC atau TFC dan kemampuan menangkal radikal bebas DPPH atau kemampuan mereduksi ion besi, hasil menunjukkan bahwa kemampuan menangkal radikal bebas DPPH dominan dikontribusi oleh TPC dan kemampuan mereduksi ion besi ditentukan oleh TPC dan TFC.